The Role of South Malang Coastal Communities in Local Wisdom-Based Environmental Management - Rahman, Arif; Putri, Bayshera Andinda; Sofiana, Elma; Syifa, Nor; Angriani, Parida (JPG (Jurnal Pendidikan Geografi), 2025)
The coastal communities of South Malang play a significant role in preserving the environment through various activities rooted in local wisdom passed down through generations. This study aims to analyze the role of the South Malang coastal communities in environmental management based on local wisdom. Using a descriptive qualitative approach, this research explores various forms of local wisdom, such as traditional customs, sustainable natural resource utilization practices, and cultural values that support environmental preservation. The findings reveal that coastal communities actively contribute to coral reef conservation, mangrove area management, and sustainable marine resource utilization by applying ecological principles. The support of local communities through traditional rituals and social norms has also proven effective in maintaining ecosystem balance. This study underscores that engaging coastal communities through a local wisdom-based approach can serve as a relevant strategy to integrate ecological and social dimensions in sustainable environmental management.